Uso de biorreguladores en el crecimiento y maduración de frutos de piña MD2 (Ananas comusus). - Padilla Laso, Wilfrido Gerardo (2015)
The objective of the present investigation was to evaluate the effect of the use of bio regulators on growth and maturation of fruits of pineapple (Ananas comosus) MD2. It is conducted in the province of Santo Domingo of the Tsachilas, Canton Santo Domingo, Km. 7 Track Quevedo, in the compound San Remo, Hacienda San Remo, located in the UTM coordinates: 17M 0677960-9921924, had duration of 5 months. The bio regulators applied were: Auxin 1L/ha-1, Gibberellin 1L/ha-1 and the combination of Gibberellin + Auxin 0.5 + 0.5 1L/ha-1. The experimental design employed was a D. B. C. A. (Design randomized complete blocks) with 4 treatments and 4 repetitions. Of the results is that the maturity of the pineapple MD2 with the implementation of the hormones after the floral induction, the maturity was presented to the 21 weeks, at which time it was suitable for the procedure of harvest and export. Protrudes the T3 treatment (Gibberellin 11L/ha-1), with fruits longer, thicker and heavier. In sugar content and translucency of the pulp treatment stands out the T4 (Auxin + Gibberellin 1L/ha-1), with fruits that are on average 15.84 degrees Brix and 1.17 translucency of the pulp. The higher marginal utility is $7705.09 USD has with the T3 treatment in which was used (Gibberellin 1L/ha-1).